Clinical Profile and Echocardiographic Changes in Patients with Newly Diagnosed Type 2 Diabetes - Jaiswal, Niraj Kumar; Karki, Manoj; Dhakal, Pushpa Raj; Dahal, Manish; Kandel, Sanjog; Shahi, Aakash; Chaudhary, Shatdal (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION The burden of type 2 diabetes is increasing in world and same is scenario in Nepal.The prevalence of T2DM in Nepal has increased from 2014 to 2020. T2DM is still a major cause of worldwide morbidity and mortality, due to its complications. A strong correlation between cardiovascular diseases and diabetes mellitus type 2 (DM) has been found. This study aimed to investigate echocardiographic features and clinical proﬁle in patients with newly diagnosed T2DM. MATERIAL AND METHODS Our study included 100 patients with newly diagnosed type 2 diabetes, presented to Medicine Department of Universal College of Medical Sciences Teaching Hospital, Bhairahawa from 1st May, 2019 AD to 30th April 2020. We included type 2 diabetes diagnosed as per American diabetes association 2018 criteria. RESULTS Males (52%) were more compared to females (44%). 28% were in age group 61-70 years, 26% in age group 41-50 years and 25% in age group 51-60 years. Abnormal thirst 42%, polyuria 38% and weight loss 32% were most common presenting symptoms with 23% having all 3 symptoms. Fifty two percent were smokers, 22% consumed alcohol, 48% had HTN and 23% cases had CAD. Fourty two cases (42%) had Left ventricular diastolic dysfunction, 25 cases (25%) had Left ventricular hypertrophy (LVH), 16 cases (16%) had RWMA others had RA/RV dilated and dilated LV/LA. CONCLUSION LVDD was most common echocardiographic ﬁnding in newly diagnosed type 2 diabetes.